2003
DOI: 10.1074/jbc.m302251200
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Causes Translocation of p47 to Membrane Ruffles through WAVE1

Abstract: Growth factors initiate cytoskeletal rearrangements tightly coordinated with nuclear signaling events. We hypothesized that the angiogenic growth factor, vascular endothelial growth factor (VEGF), may utilize oxidants that are site-directed to a complex critical to both cytoskeletal and mitogenic signaling. We identified the WASP-family verprolin homologous protein-1 (WAVE1) as a binding partner for the NADPH oxidase adapter p47 phox within membrane ruffles of VEGF-stimulated cells. Within 15 min of VEGF stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 41 publications
6
71
1
1
Order By: Relevance
“…These data contrast with those of Wu et al (78) who showed that VEGF-mediated phosphorylation of JNK was oxidasedependent. Moreover, previous studies in HUVEC have demonstrated a role for ROS in VEGF-mediated activation of ERK1/2 in HUVEC and porcine aortic endothelial cells (23,36).…”
Section: Discussioncontrasting
confidence: 56%
“…These data contrast with those of Wu et al (78) who showed that VEGF-mediated phosphorylation of JNK was oxidasedependent. Moreover, previous studies in HUVEC have demonstrated a role for ROS in VEGF-mediated activation of ERK1/2 in HUVEC and porcine aortic endothelial cells (23,36).…”
Section: Discussioncontrasting
confidence: 56%
“…Molecular linkage between actin cytoskeleton and NAD(P)H oxidase has been demonstrated. [23][24][25][26] In ECs, Wu et al 27 reported that VEGF promotes p47 phox translocation to membrane ruffles via direct interaction with WAVE1, a promoter of the actin nucleation complex, which in turn activates NAD(P)H oxidase. Qian et al 28 showed that arsenicinduced NAD(P)H oxidase activation and EC migration are suppressed by cytochalasin D and jasplakinolide.…”
Section: Discussionmentioning
confidence: 99%
“…Several signalling pathways have been implicated in the formation of dorsal Journal of Cell Science 123 (8) ruffles downstream from RTKs, including PI3K (Dharmawardhane et al, 2000;Scaife and Langdon, 2000) and Rac (Palamidessi et al, 2008) Dowrick et al, 1993;Krueger et al, 2003;Orth et al, 2006;Wu et al, 2003). Gab1 is recruited to each of these RTKs, where it participates in the activation of downstream signalling pathways, including PI3K and Rac (Dance et al, 2006;Gu and Neel, 2003;Jackson et al, 2004;Laramee et al, 2007;Maroun et al, 1999a;Rakhit et al, 2000;Rodrigues et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal ruffles form in response to stimulation by growth factors such as HGF, EGF, PDGF-bb and vascular endothelial growth factor (VEGF) (Buccione et al, 2004;Dowrick et al, 1993;Wu et al, 2003) and require regulators of actin polymerisation (Buccione et al, 2004) and Rac activity (Krueger et al, 2003;Lanzetti et al, 2004;Palamidessi et al, 2008;Ridley et al, 1992;Suetsugu et al, 2003;Wu et al, 2003). Formation of dorsal ruffles requires localisation of activated Rac to the plasma membrane; for instance, the small GTPase Rab5 is required for HGF-induced dorsal ruffles, as it trafficks activated Rac to the plasma membrane (Lanzetti et al, 2004;Palamidessi et al, 2008), indicating that regulators of Rac localisation to the membrane are crucial for dorsal ruffle formation.…”
Section: Introductionmentioning
confidence: 99%